No Equal Justice - David Cole (My University, 2016)
The most telling image from the most widely and closely watched criminal trial of our lifetime is itself an image of people watching television.  On one half of the screen black law students atHoward Law School cheer as they watch the live coverage of a Los Angeles jury acquitting O.J. Simpson of the double murder of his exwife and her friend.  On the other half of the screen, white students as George Washington University Law School sit shocked in silence as they watch the same scene.  The split-screen image captures in a moment the division between white and black   Americans on the question of O.J. Simpson’s guilt.  And that division in turn reflects an even deeper divide on the issue of the fairness and legitimacy of American criminal justice.

Reseña: The most telling image from the most widely and closely watched criminal trial of our lifetime is itself an image of people watching television.  On one half of the screen black law students atHoward Law School cheer as they watch the live coverage of a Los Angeles jury acquitting O.J. Simpson of the double murder of his exwife and her friend.  On the other half of the screen, white students as George Washington University Law School sit shocked in silence as they watch the same scene.  The split-screen image captures in a moment the division between white and black   Americans on the question of O.J. Simpson’s guilt.  And that division in turn reflects an even deeper divide on the issue of the fairness and legitimacy of American criminal justice.